Unification and the Quantum Hypothesis in 1900–1913. Issue 5 (December 2015) - Kao, Molly
Abstract : In this article, I consider some of the first appearances of a hypothesis of quantized energy between the years 1900 and 1913 and provide an analysis of the nature of the unificatory power of this hypothesis in a Bayesian framework. I argue that the best way to understand the unification here is in terms of informational relevance: on the assumption of the quantum hypothesis, phenomena that were previously thought to be unrelated turned out to yield information about one another on the basis of agreeing measurements of the numerical value of Planck's constant.